2005
DOI: 10.1038/sj.ejcn.1602209
|View full text |Cite
|
Sign up to set email alerts
|

Lung function and blood levels of copper, selenium, vitamin C and vitamin E in the general population

Abstract: Background: Increased dietary intake of antioxidants has been associated with higher lung function, but few studies have used biological markers of antioxidant intake. Objective: This study aimed to determine if antioxidant status, as measured by blood levels, influences lung function. Design: Using a random subsample of 479 participants, aged 18-65 y old, from a larger cross-sectional observational study, the association of forced expiratory volume in 1 s (FEV 1 ) with plasma copper, vitamin C, vitamin E and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
34
1
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 39 publications
2
34
1
1
Order By: Relevance
“…Another study found that lower respiratory function and higher serum copper concentration were associated [7]. Similar to this study, our study found that serum copper levels and lung function are associated.…”
Section: Discussionsupporting
confidence: 91%
“…Another study found that lower respiratory function and higher serum copper concentration were associated [7]. Similar to this study, our study found that serum copper levels and lung function are associated.…”
Section: Discussionsupporting
confidence: 91%
“…For example, higher serum Se levels are positively associated with higher FEV1 and are protective for lung function [3,4]. In addition, several epidemiological studies have observed lowered serum Se levels in asthma patients [5][6][7][8], yet the level of Se deficiency that is associated with asthma is not clearly established.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been suggested that serum Se, another antioxidant, may have pulmonary protective effects but its reported associations with pulmonary function are based on a limited number of studies (11,15) .…”
mentioning
confidence: 99%